Pengaruh Kualitas Produk, Persepsi Harga, dan Lokasi Terhadap Kepuasan Pelanggan (Pada Roemah Coffee Eatery & Hub) - Vera Verina; Efiani (Panorama Nusantara, 2022)
This study aims to ascertain the impact of product quality, price perception, and location on consumer satisfaction at Roemah Coffee Eatery & Hub. The research method used is multiple linear regression analysis with purposive sampling technique. Data was collected by giving questionnaires to 100 respondents with the criteria of customers who had visited at least 2 or more times to Roemah Coffee Eatery & Hub. From the 120 respondents, as many as 20 respondents were used to test the validity and reliability. Meanwhile, 100 respondents were used for classical assumption testing, multiple regression analysis, t test and F test, and analysis of the coefficient of determination (R2). From the results it can be concluded that product quality has a positive and partially significant effect on customer satisfaction. Price perception has a positive and partially significant effect on customer satisfaction. Location has a positive and significant effect partially on customer satisfaction. Product quality, price perception, and location have a simultaneous positive and significant effect on customer satisfaction.